EFFECTS OF THE ADDITION OF AQUEOUS LIQUORICE (Glycyrrhiza glabra) EXTRACT TO DRINKING WATER IN THE PRODUCTION PERFORMANCE, CARCASS CUTS AND INTESTINAL HISTOMORPHOLOGY OF BROILER CHICKENS - & et al., Beski (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was undertaken to investigate the effect of aqueous liquorice extract (ALE) on the growth performance, carcass cuts and intestinal histomorphology of broiler chickens between hatch and 35 days of age. A total of 160-d old (Ross 308) broiler chicks were randomly assigned to 4 treatments, each with 4 replicates, 10 birds per replicate. Four different levels of aqueous liquorice (0, 0.5, 0.7 and 0.9g) were administrated to a liter of drinking water and offered to the birds throughout the entire experimental period. Across the 35 days of trial, administration of ALE to the drinking water resulted in higher (P<0.05) body weight and weight gain. While, feed intake, water intake and FCR did not influence by ALE administration. On the other hand, there was no significant effect of the ALE on carcass cuts, visceral organs and intestinal histomorphology. The study demonstrated that ALE could be administrated to the drinking water of broilers between 0.5 and 0.9g/ liter. However, it would be more economical to use the medium level of ALE (0.7g/ liter) to achieve better results.